Comparison of surgeon and pathologist total mesorectal excision grade after rectal cancer resection: A single institution analysis. Issue 6 (15th February 2023) - Kato, Patrick J.; Kanters, Arielle E.; Rivard, Samantha J.; Hendren, Samantha; Ramm, Carole; Albright, Jeremy; Schumaker, Kate E.; Cleary, Robert K.
Abstract: Background: A Michigan Surgical Quality Collaborative Colorectal Cancer Project initiative sought to increase adoption of surgeon total mesorectal excision (TME) grading through standardized education and synoptic operative reporting. Our study aim was to assess initiative impact and level of agreement between surgeon and pathologist‐determined TME grades. Methods: This is a retrospective comparison of surgeon and pathologist TME grades before and after initiative implementation using a prospectively maintained enhanced recovery colorectal surgery database. Results: There were 112 TMEs before, and 53 TMEs following initiative implementation. There was a significant increase in surgeon TME‐grade reporting in the postinitiative period (25.0% pre‐ vs. 81.1% post‐, p  < 0.001). Pathologist TME‐grade reporting was high in both time periods and there was no significant change (91.1% pre‐ vs. 88.7% post‐, p  = 0.84). Surgeon and pathologist agreement was 59.3% in the preinitiative period ( Κ  "minimal"   0.356) and 65.0% in the postinitiative period ( Κ  "moderate" = 0.605, p  = 0.827). There was no significant association between clinical T‐stage and surgeon or pathologist TME grade. Conclusion: Surgeon TME grading improves with education and synoptic operative reporting. There is only moderate agreement between surgeon and pathologist, a finding that requires further study. Organized regional initiatives are effective at implementing rectal cancer management quality improvement.